2012
DOI: 10.1523/jneurosci.3300-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

SRPK2 Phosphorylates Tau and Mediates the Cognitive Defects in Alzheimer's Disease

Abstract: Serine-arginine protein kinases 2 (SRPK2) is a cell cycle-regulated kinase that phosphorylates serine/arginine domain-containing proteins and mediates pre-mRNA splicing with unclear function in neurons. Here, we show that SRPK2 phosphorylates tau on S214, suppresses tau-dependent microtubule polymerization and inhibits axonal elongation in neurons. Depletion of SRPK2 in dentate gyrus inhibits tau phosphorylation in APP/PS1 mouse and alleviates the impaired cognitive behaviors. The defective LTP in APP/PS1 mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 46 publications
1
56
0
2
Order By: Relevance
“…In contrast to Srpk1, which is expressed ubiquitously, Srpk2 exhibits particularly high expression levels in the nervous system suggestive of a neuronspecific function (Wang et al 1998). Interestingly, Srpk2 was found to be up-regulated in brains of APP/PS1 transgenic mice, a model for Alzheimer's disease (Hong et al 2012). In that study, knockdown of Srpk2 in APP/PS1 mice alleviated memory deficits and increased synaptic plasticity.…”
Section: Discussionmentioning
confidence: 84%
“…In contrast to Srpk1, which is expressed ubiquitously, Srpk2 exhibits particularly high expression levels in the nervous system suggestive of a neuronspecific function (Wang et al 1998). Interestingly, Srpk2 was found to be up-regulated in brains of APP/PS1 transgenic mice, a model for Alzheimer's disease (Hong et al 2012). In that study, knockdown of Srpk2 in APP/PS1 mice alleviated memory deficits and increased synaptic plasticity.…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, both proteins regulate Tau pathological functions via either phosphorylation or cleavage (Hong et al, 2012; Zhang et al, 2014; Zhang et al, 2015). Accordingly, we hypothesize that these two pathways are linked in that SRPK2 might regulate delta-secretase via phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, SRPK2 can be activated by Aβ, and activated SRPK2 phosphorylates Tau on S214, suppressing Tau-dependent microtubule polymerization and inhibiting axonal elongation in neurons. SRPK2 activity is augmented in the neurons of Alzheimer’s disease (AD) mice and patients (Hong et al, 2012), strongly implicating a role for SRPK2 in AD disease etiology and pathogenesis. Our previous work also showed that SRPK2 phosphorylates SC35, a SR splicing factor located in nuclear speckles (Jang et al, 2009), and it has recently been reported that dysregulated RNA processing with accumulation of unspliced RNA species occurred in human AD and MCI (mild cognitive impairment) patients (Bai et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Electrophysiological analysis was carried out as previously described (Hong et al, 2012). Briefly, vehicle-and 7,8-DHFtreated 5XFAD mice were anaesthetized with isoflurane, decapitated, and the hippocampi were cut into 400-mm thick transverse slices with a vibratome.…”
Section: Electrophysiological Analysismentioning
confidence: 99%